Trinitariese verbeelding en post-apartheid Suider-Afrika: fragmente oor dogmatisering en dosering - R. Venter (Acta Theologica)
A proposal is made about the teaching of Dogmatics in Southern Africa. An alternative teaching practice is required by the radical social, intellectual and theo-ecclesial changes.New sentiments have emerged which contributed to a change in the conception of the dogmatological task. The dogmatician linguistically constructs a symbolic universe that exerts an ethical impact. The notion of a “trinitarian imagination” is espoused to articulate the entire Christian vision from the reality of God’s trinitarian identity. The existence of possible challenges to such a proposal is acknowledged. When applied to the classroom it implies that students should be mentored to acquire the skill of trinitarian rhetoric; that the selection of study material has become tremendously problematic; and finally, that learning should become much more experimental. The conviction is expressed that such a trinitarian orientation could contribute in a positive way to the Southern Africa context.